2015
DOI: 10.1519/jsc.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sprint Ability and Loaded/Unloaded Jump Tests in Elite Sprinters

Abstract: The neuromechanical determinants of sprint running performance have been investigated in team sports athletes and non-elite sprinters. The aim of this study was to quantify the relationships between kinetic and performance parameters, obtained in loaded and unloaded vertical and horizontal jumps, and sprinting in elite athletes. Twenty-two sprinters performed squat jumps, countermovement jumps, horizontal jumps, and jump squats with different loads on a force platform, in addition to a 50-m sprint. Results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
95
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 15 publications
16
95
5
1
Order By: Relevance
“…Maulder and Cronin (2005) found that horizontal jumps (horizontal squat, counter-movement and repetitive jumps) have greater predictive ability for 20 m sprint performance. In agreement with this, others have found horizontal jump tests (i.e., single and triple hop tests, standing long jumps) to be better predictors of short sprint performance (0 to 50 m) than vertical jump tests (i.e., squat and counter-movement jumps) (Habibi et al, 2010;Loturco et al, 2015a, Robbins, 2012. However, Robbins and Young (2012) found that the vertical jump test was more strongly related to the flying 18.3 sprint test, whereas Lorturco et al, (2015b) found CMJ height had a marginally stronger correlation to 100m sprint time than horizontal jump distance (R=-0.85 vs. -0.81) and thus, suggests that characteristics associated with vertical force production may be more important for maximum speed.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 56%
“…Maulder and Cronin (2005) found that horizontal jumps (horizontal squat, counter-movement and repetitive jumps) have greater predictive ability for 20 m sprint performance. In agreement with this, others have found horizontal jump tests (i.e., single and triple hop tests, standing long jumps) to be better predictors of short sprint performance (0 to 50 m) than vertical jump tests (i.e., squat and counter-movement jumps) (Habibi et al, 2010;Loturco et al, 2015a, Robbins, 2012. However, Robbins and Young (2012) found that the vertical jump test was more strongly related to the flying 18.3 sprint test, whereas Lorturco et al, (2015b) found CMJ height had a marginally stronger correlation to 100m sprint time than horizontal jump distance (R=-0.85 vs. -0.81) and thus, suggests that characteristics associated with vertical force production may be more important for maximum speed.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 56%
“…After the warm-up, loaded-squat jump movement was executed with an load that corresponds to 40% of body weights of the subjects by using free weight. During test, athletes must bring their knees to the flexion situation until their thighs were straight to floor from stationary situation, to jump quickly without losing touch between their shoulders and bar following the start command and to repeat it 3 times (Loturco et al, 2015). These movements were repeated when these requirements were not fulfilled.…”
Section: Methodsmentioning
confidence: 99%
“…After warm-up activities, the subjects were exposed to loaded squat jump test by using external loads corresponding to 40% of their body weight. In applying test protocols, the subjects were asked to bring their knees in flexion from a static position until their thighs became parallel to the ground and to jump as fast as possible without losing their shoulder contact with the barbell after the command and to repeat that practice three times (Loturco et al, 2015). The practice was repeated when the specified test rules were not followed; because in addition to the external load used in the application of the test, it was needed to move body weight and by that means, kinetic-kinematic parameters such as velocity and power were determined with the individual's acceleration competency of total mass comprising external load and body weight (Cormie et al, 2007).…”
Section: Methodsmentioning
confidence: 99%